Hidden players of COVID-19: the evolving roles of SARS-CoV-2 accessory proteins - Padilla-Blanco, Miguel; García-García, Tránsito; Grigas, Juozas; López-Ayllón, Blanca D.; Garrido, Juan J.; Oliva, María A.; Montoya, María (Frontiers in Immunology, 2025)
SARS-CoV-2 accessory proteins (APs), particularly ORF3a and ORF9b, have emerged as key modulators of host-pathogen interaction and potential contributors to long COVID. Of the 13 predicted APs, only nine are expressed during infection – termed Infection-related APs – while the remaining are classified as Putative APs. Despite this distinction, extensive gene overlap among APs underscores the remarkable adaptability of SARS-CoV-2 viral genome. This review delves into the diverse roles of the original Wuhan APs and their Omicron counterparts in shaping host immunity, with an emphasis on their ability to suppress type I interferon (IFN-I) signalling, modulate cellular metabolism, and trigger inflammatory/apoptotic pathways. By integrating immunopathological insights with evolutionary dynamics and structural perspectives, this review provides a comprehensive understanding of the mechanism underlying Omicron’s reduced pathogenicity and highlights promising, yet unexplored, therapeutic targets within the SARS-CoV-2 accessory proteome.